Malignant ameloblastoma metastasis to the lung: a case report - Senra, Giselle Segnini [UNESP]; Pereira, Andresa Costa [UNESP]; Santos, Lucio Murilo dos [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Brandão, Adriana Aigotti Haberbeck [UNESP] (Mosby-elsevier, 2008)
Ameloblastoma is an odontogenic tumor, usually benign, which rarely metastasizes to distant organs. The case of a 27-year-old white woman is described, who presented a metastatic pulmonary ameloblastoma 7 years after the removal of a mandibular ameloblastoma. She presented no pulmonary symptoms, but a lung nodule was found in a chest x-ray during a routine check-up for job admission. Computed tomography (CT) revealed a 2-cm well-defined solitary round nodule without calcifications, leading to the hypothesis of a metastatic tumor. Clinical and CT investigation confirmed no ameloblastoma recurrence in the jaw and no other primary tumor. The diagnosis of metastatic ameloblastoma was confirmed by microscopic evaluation of the pulmonary nodule.